Extreme natural and man-made events and human adaptive responses mediated by information and communication technologies' use: A systematic literature review - Gaspar, Rui (2019)
Information and Communication Technologies (ICTs) are nowadays an interactive means through which humans respond to potentially stressful extreme events (e.g., natural or technological disasters). Despite growing research and reviews on ICTs' role, these often follow an event-specific approach, describing how or what people respond without explaining why they respond as they do, limiting a broader comprehension of human adaptation processes. Therefore, a systematic literature review on natural and man-made extreme events sought to identify: how people respond during extreme events through ICTs devices/platforms use, what ICTs-mediated responses take place during these, and why they respond in the way they do (i.e., the responses' adaptive functions). A database search identified 60 articles through three inclusion criteria: (1) report of events deviating in socio-physical parameters from “normal” circumstances; (2) type of ICTs devices/platforms used; and (3) longitudinal data collection method. A theory-driven content analysis showed that different ICT platforms may be used for different adaptive functions with a predominant function of allowing coordinating an individual's actions with the contingencies in the environment, through approach (e.g., problem solving) and avoidance (e.g., escape) ways of coping. ICTs seemingly are an important data source and means in enabling socio-physical systems to effectively respond to extreme events. PROSPERO CRD42016042455.